1997
DOI: 10.1128/jb.179.23.7456-7461.1997
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of serine hydroxymethyltransferase from Sulfolobus solfataricus

Abstract: Serine hydroxymethyltransferase (SHMT) catalyzes the reversible cleavage of serine to glycine with the transfer of the one-carbon group to tetrahydrofolate to form 5,10-methylenetetrahydrofolate. No SHMT has been purified from a nonmethanogenic Archaea strain, in part because this group of organisms uses modified folates as the one-carbon acceptor. These modified folates are not readily available for use in assays for SHMT activity. This report describes the purification and characterization of SHMT from the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Besides catalyzing its main physiological reaction of SHMT activity, the enzyme is known to catalyze a broad range of reactions, including a retro-aldol cleavage of 3-hydroxy-amino acids, transamination and decarboxylation [7,8]. Although SHMTs from many prokaryotes and eukaryotes have been studied [11][12][13][14][15][16][17], in-depth investigation has focused only on SHMTs from rabbit and sheep liver, as well as E. coli and Bacillus stearothermophilus [6,7,11,18,19].…”
mentioning
confidence: 99%
“…Besides catalyzing its main physiological reaction of SHMT activity, the enzyme is known to catalyze a broad range of reactions, including a retro-aldol cleavage of 3-hydroxy-amino acids, transamination and decarboxylation [7,8]. Although SHMTs from many prokaryotes and eukaryotes have been studied [11][12][13][14][15][16][17], in-depth investigation has focused only on SHMTs from rabbit and sheep liver, as well as E. coli and Bacillus stearothermophilus [6,7,11,18,19].…”
mentioning
confidence: 99%
“…Moreover, the purification of the enzyme from Archaea that thrive in extreme environments is complicated by the difficulty of growing these organisms in a laboratory. Two reports of purified SHMT activity, from Methanobacterium thermoautotrophicum (4), recently renamed Methanothermobacter marburgensis (5), and from Sulfolobus solfataricus (6), with limited structural and functional characterization, have been made. In the first report, the enzyme was proposed to function in vivo in the direction of serine biosynthesis.…”
mentioning
confidence: 99%
“…volcanii seems to be the exception among the archaea. In the methanogenic and thermoacidophilic archaea, C 1 transfer reactions have been shown to be carried out either with modified folates or in the absence of folate derivatives (Nyce and White, 1996; Delle Fratte et al ., 1997; White, 1997b). Moreover, inspection of the five complete archaeal genome sequences published to date did not reveal sequence homologies to DHFR or to bacterial and eukaryotic thymidylate synthases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that considerable amounts of folates exist in the extremely halophilic archaea, whereas the methanogenic and thermoacidophilic archaea contain, in their place, a variety of modified folates (White, 1988; 1991; 1997a; Worrell and Nagle, 1988). In some archaea, purine biosynthesis requires neither folates nor modified folates (White, 1997b), whereas the biosyntheses of thymidine (Nyce and White, 1996) and glycine (Delle Fratte et al ., 1997) involve only modified folates.…”
Section: Introductionmentioning
confidence: 99%